2022
DOI: 10.3389/fpubh.2022.853453
|View full text |Cite
|
Sign up to set email alerts
|

Health care provider's experience and perspective of cervical cancer screening in Singapore: A qualitative study

Abstract: BackgroundIn Singapore, the current cervical cancer screening (CCS) coverage rate of 48% falls below the national target of 70%. Health care providers (HCPs) play a critical role in promoting CCS uptake. However, there is limited understanding of the perspectives of HCPs regarding CCS. Hence, we aimed to understand the challenges encountered by HCPs delivering CCS in different care settings in the Singapore health system. We also aimed to explore perspectives on newer features of CCS such as self-sampling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Yet, the national screening program uses PGT, which provides no information on these HPV genotypes. In an interview with Singapore healthcare providers, the value of specific HPV genotyping beyond HPV16/18 was highlighted [ 19 ]. For example, with XGT, the prevalence of specific non-HPV16/18 genotypes can be established, and those that pose a lower risk can be identified for less intensive management [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the national screening program uses PGT, which provides no information on these HPV genotypes. In an interview with Singapore healthcare providers, the value of specific HPV genotyping beyond HPV16/18 was highlighted [ 19 ]. For example, with XGT, the prevalence of specific non-HPV16/18 genotypes can be established, and those that pose a lower risk can be identified for less intensive management [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an interview with Singapore healthcare providers, the value of specific HPV genotyping beyond HPV16/18 was highlighted [ 19 ]. For example, with XGT, the prevalence of specific non-HPV16/18 genotypes can be established, and those that pose a lower risk can be identified for less intensive management [ 19 ]. Based on the above, we undertook a systematic evaluation of the benefits and consequences of using XGT in the national screening program.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, our study is one of the first to explicitly quantify the efficient gains through age‐ and genotype‐specific algorithms under uniform primary HPV testing for a vaccinated cohort. We identified two studies (the United States and Singapore) that found extended genotyping (three HPV groups) was likely to be considered cost‐effective over partial genotyping; however, they did not consider the potential of age‐specific algorithms alongside extended genotyping 7,8 …”
Section: Discussionmentioning
confidence: 99%
“…Following their first adolescent‐vaccinated cohort entering screening in 2022, Norway is considering extended HPV genotyping and age‐specific triage approaches. To our knowledge, although extended genotyping has been examined, 6–8 there are no cost‐effectiveness analyses or harm–benefit evaluations that combine both age and multiple extended genotyping triage algorithms. Therefore, the aim of this study was to estimate the health impact, harms and cost‐effectiveness of novel primary HPV triage approaches for a highly vaccinated cohort of women initiating screening in 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation